Muscle responses to radicular stimulation during lumbo-sacral dorsal rhizotomy for spastic diplegia: Insights to myotome innervation. Issue 5 (May 2020) - Georgoulis, George; Sindou, Marc
Highlights: Study shows important inter-individual variability in myotome innervation among patients. Most muscles have multi-radicular innervation. Root territories strongly overlap, not only under dorsal but also ventral stimulation at threshold. Abstract: Objective: Most of knowledge on muscle radicular innervation was from explorations in root/spinal cord pathologies. Direct and individual access to each of the lumbar-sacral -ventral and dorsal- nerve roots during dorsal rhizotomy for spastic diplegia allows precise study of the corresponding muscle innervation. Authors report the lumbo-sacral segmental myotomal organization obtained from recordings of muscle responses to root stimulation in a 20-children prospective series. Methods: Seven key-muscles in each lower limb and anal sphincter were Electromyography (EMG)-recorded and clinically observed by physiotherapist during L2-to-S2 dorsal rhizotomy. Ventral roots (VR), for topographical mapping, and dorsal roots (DR), for segmental excitability testing, were stimulated, just above threshold for eliciting muscular response. Results: In 70% of the muscles studied, VR innervation was pluri-radicular, from 2-to-4 roots, with 1 or 2 roots being dominant at each level. Overlapping was important. Muscle responses to DR stimulation were 1.75 times more extended compared to VR stimulation. Inter-individual variability was important. Conclusions: Accuracy of root identification and stimulation with the used method brings some more precise information to radicular functional anatomy. Significance: Those neurophysiological findings plead for performing Intra-Operative Neuromonitoring when dealing with surgery in the lumbar-sacral roots.